Diurnal Fluctuation in Haematological Parameters of the Domestic Fowl in the Hot Humid Tropics - Azeez, O.I.; Oyagbemi, A.A.; Oyewale, J.O. (International Journal of Poultry Science, 2009)
Diurnal fluctuation in haematological parameters such as packed cell volume (PCV), red blood cell (RBC) count, haemoglobin concentration (Hb), mean corpuscular volume (MCV), mean corpuscular haemoglobin (MCH), mean corpuscular haemoglobin concentration (MCHC) and erythrocyte osmotic fragility of the domestic fowl in the hot humid tropics was investigated using Nera Black cocks. Blood samples were collected from the birds at 6:00 am, 10:00 am, 2:00 pm, 6:00 pm, 10:00 pm and 2:00 am during a 12-hour light and a 12-hour dark period. PCV showed considerable diurnal variation with the lowest value obtained at 10:00 am and the peak value recorded during the early morning (2:00 am). RBC, Hb, MCH and MCHC values also varied according to the time of the day, with the lowest values observed at 2:00 pm, probably as a result of haemodilution following increased feed and water consumption at this period of the day. Peak values for RBC, Hb, MCH and MCHC were observed at 10:00 pm when the birds were already roosting (during the dark phase of the day) as a result of which physical and metabolic activities were generally lowered. Haemoconcentration so produced might be responsible for the higher haematological parameters during the night because the birds were neither eating nor drinking water at this period of the day. Erythrocyte osmotic fragility at 0.3% NaCl concentration was also significantly higher (P < 0.05) at 6:00 am than at any other period of the day.